Out of the inkwell : Max Fleischer and the animation revolution - Fleischer, Richard (Lexington : University Press of Kentucky, 2005)
Presents a comprehensive biography of celebrated animator, Max Fleischer, and chronicles the life and career of the artist who created the popular "Betty Boop," "Popeye," and "Superman" cartoons.
Includes index.
Booklist, May 2005
Choice, January 2006
Adult
Keywords: Fleischer, Max, -- 1883-1972.; Animators -- Biography